Combining methods in legal research - Mohamed, Khadijah (Medwell Journal, 2016)
Traditional legal research normally employs doctrinal method. This method involves research into the law and legal concepts prominently through the study of legal rules; by analysing court judgments and statutes with little or no reference to the world outside the law.Over the years, doctrinal research continues to be the most widely used method in legal research.However, this is not always the case particularly when legal research engages law as social phenomena.The sociology of law basically studies causal, structural and functional connections between legislation, legal practice, legal research and a number of social factors. Where the existence of law is correlated with social existence, empirical data is usually supplemented to traditional legal research.The use of empirical evidence in this context is considered as producing generally more reliable data.The objective of this study is to assess the application of combining research methods approach in legal education research, based on two broad traditions: doctrinal and socio-legal methods.The study argues that no particular method is privileged over any other. Rather, the choice must be driven by the research questions.The study examines the definition, aims and basic features of each approach. Brief distinction of research concepts used between legal and social science research is also made. The study concludes that due to the wide variety of issues still to be explored within legal research, combination of methods in legal research will therefore be essential in the future.